2018
DOI: 10.1590/1809-4430-eng.agric.v38n1p7-12/2018
|View full text |Cite
|
Sign up to set email alerts
|

Similitude and Thermal Performance on Non-Conventional Roofs

Abstract: The objectives of this study were to evaluate the thermal comfort and the similitude between prototypes and reduced models, using non-conventional coverage with green roof and expanded clay aggregate, supported on wood frame structure. For this, were determined the Black Globe Temperature and Humidity Index (BGHI), the Human Discomfort Index (HDI), Effective Temperature (ET), Air Temperature (Tair) and Radiant Thermal Load (RTL), from March 2013 to December 2014. The results showed that there were no statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Thus, it can be concluded that the internal environment of the sheds was out of the comfort conditions for broilers during the entire trial period, demonstrating the importance of the study of thermal comfort in the facilities, as well as the application of different techniques to improve animal welfare Ribeiro et al, 2016;Sampaio et al, 2018;Coelho et al, 2019;Lourençoni et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…Thus, it can be concluded that the internal environment of the sheds was out of the comfort conditions for broilers during the entire trial period, demonstrating the importance of the study of thermal comfort in the facilities, as well as the application of different techniques to improve animal welfare Ribeiro et al, 2016;Sampaio et al, 2018;Coelho et al, 2019;Lourençoni et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…For the generation of regionalized climate scenarios, the Statistical DownScaling Model (SDSM) technique will be applied to the projections of four Global Climate Models (GCMs), in order to synthetize time series of rainfall and temperature for 97 weather stations spatially distributed along the NEB. For the thermal comfort index, we resort to the one proposed by Ono & Kawamura (1991), a dimensionless mathematical expression recommended for intertropical regions, which takes into account the air temperature and relative humidity (represented in the equation by the dew point temperature), being applicable to dressed adult people at rest and submitted to a slight motion of the air (Sampaio et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The impact that a rural production building can cause on the production process itself, on the product and the workers, is very expressive. Especially in animal production, the quality of the physical environment 2,3,11,12,[21][22][23][24][25][26][27][28][29][30] (rooms, population density, construction materials, the ease of nutritional and sanitary management) and the quality of the indoor environment (pollutant gases, particulate materials, microorganisms, temperature and relative humidity, ventilation 11,[31][32][33] ) are distinctive factors in the quality of the process and product.…”
Section: Introductionmentioning
confidence: 99%